John Steinbeck papers - Steinbeck, John, 1902-1968.; Ricketts, Edward Flanders, 1897-1948.; Steinbeck, John, 1902-1968.; Steinbeck, John, 1902-1968.
Typescripts with holograph corrections of The Grapes of Wrath (1940) and Sea of Cortez (1941), the latter coauthored by Edward Flanders Ricketts, together with related material; and letter (1962 March 24) written by Steinbeck to Cynthia and Robert Wallsten, describing Steinbeck's stay on Capri Island, Italy.
Author. Full name: John Ernst Steinbeck.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Wallsten, Cynthia Rogers, -- -1971 -- Correspondence; Wallsten, Robert, -- 1912- -- Correspondence; American literature; Capri Island (Italy) -- Description and travel; Italy -- Description and travel; Authors